Effect of Ethylene Glycol Concentration and Length of Exposure on In Vitro Fertility of Bovine Oocyte - Sri Wahjuningsih; Suhartojo Hardjopranjoto; Sutiman Bambang Sumitro (Jurnal Kedokteran Hewan, 2010)
The purpose of the study was to determine the influence of the concentration of ethylene glycol (EG) and length of exposure to levels of bovine oocytes in vitro fertility. This research was conducted using a completely randomized design factorial 5x3 with 7 replicates. The first factor was the concentration of cryoprotectants EG 10, 20, 30, 40, and 50%. The second factor was the length of exposure 1, 3, and 5 minutes. The results showed that the concentration of EG and the length of exposure were effect on fertilized oocytes (P0.05). The level of oocytes in vitro fertility after vitrification in 30% EG and long exposure to 3 minutes did not different (P0.05) compared to fresh oocytes, while the EG treatment 10, 20, 40, and 50% significantly showed a lower fertility rate than the 30% EG (P0.05). It was concluded that the concentration of EG and length of exposure were effect on fertilized oocytes. The highest oocytes in vitro fertility level were found in 30% EG concentration with 3 minutes exposure time.